Geometric no-arbitrage analysis in the dynamic financial market with transaction costs - Wanxiao Tang; Jun Zhao; Peibiao Zhao (Journal of Risk and Financial Management, 2019)
The present paper considers a class of financial market with transaction costs and constructs a geometric no-arbitrage analysis frame. Then, this paper arrives at the fact that this financial market is of no-arbitrage if and only if the curvature 2-form of a specific connection is zero. Furthermore, this paper derives the fact that the no-arbitrage condition for the one-period financial market is equivalent to the geometric no-arbitrage condition. Finally, an example states the equivalence between the geometric no-arbitrage condition and the existence of the solutions for a maximization problem of expected utility.
Keywords: 330; geometric no-arbitrage; transaction cost; bid-ask spread